A prospective study of the immediate and delayed adverse events following intravenous immunoglobulin infusions. Issue 8 (25th April 2006) - Singh-Grewal, D; Kemp, A; Wong, M
Abstract : Aim: To document the incidence of immediate and delayed adverse events (AE) following intravenous immunoglobulin (IVIG) infusion in children. Methods: Immediate and delayed adverse events were prospectively recorded for 345 infusions in 58 children receiving IVIG for immunodeficiency (n = 33) or immunomodulation (n = 25). For each infusion adverse events were documented during the infusion and by follow up interview 4–7 days later. Results: Immediate adverse events occurred in 10.3% and delayed adverse events in 41.4% of children treated during the study period. Three and a half per cent of the infusions were associated with immediate AE and 20.9% with delayed adverse events. Headache was the most common delayed AE, occurring in 24.1% of patients and 12.8% of infusions. Conclusions: Delayed adverse events to IVIG infusions are common in children. They occur more frequently than immediate adverse events and are the cause of significant morbidity. Recognition of the high frequency of delayed adverse events is important in the care of children receiving IVIG therapy.